β cell responses to inflammation - Sahar Usmani-Brown; Ana Luisa Perdigoto; Nathalie Lavoie; Pamela Clark; Maria Korah; Jinxiu Rui; Gabriel Betancur; Kevan C. Herold (Elsevier, 2019)
Background: The extended and clinically silent progression of Type 1 diabetes (T1D) creates a challenge for clinical interventions and for understanding the mechanisms that underlie its pathogenesis. Over the course of the development of Type 1 diabetes, studies in animal models and of human tissues have identified adaptive changes in β cells that may affect their immunogenicity and susceptibility to killing. Loss of β cells has traditionally been identified by impairment in function but environmental factors may affect these measurements. Scope of Review: In this review we will highlight features of β cell responses to cell death, particularly in the setting of inflammation, and focus on methods of detecting β cell death in vivo. Major conclusions: We developed an assay to measure β cell death in vivo by detecting cell free DNA with epigenetic modifications of the INS gene that are found in β cells. This assay has robust technical performance and identifies killing in individuals at very high risk for disease, but its ability to identify β cell killing in at-risk relatives is limited by the short half-life of the cell free DNA and the need for repeated sampling over an extended course. We present results from the Diabetes Prevention Trial-1 using this assay. In addition, recent studies have identified cellular adaptations in some β cells that may avoid killing but impair metabolic function. Cells with these characteristics may aggravate the autoimmune response but also may represent a potentially recoverable source of functional β cells. Keywords: Beta cells, Apoptosis, Death, Type 1 diabetes, Inflammation, Methylation